2017
DOI: 10.1039/c7ta08127h
|View full text |Cite
|
Sign up to set email alerts
|

Titanium alkylphosphate functionalised mesoporous silica for enhanced uptake of rare-earth ions

Abstract: Solid-phase adsorbents for rare-earth ions are prepared by covalently binding organophosphate ligands on mesoporous silica via a versatile metal(iv)–O–P linkage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Previously, we reported a group of titanium(IV) alkyl-phosphate grafted silica materials that retain Ln 3+ in a solvating extraction manner. 21 The addition of nitrate salts significantly enhanced the uptake of Nd 3+ and Dy 3+ on these grafted materials, thereby suggesting that the uptake mechanism follows eq 4 . However, the addition of 5 M NH 4 NO 3 inhibited the Ln 3+ uptake on the TiP_0:1 material ( Figure S3 ).…”
Section: Results and Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previously, we reported a group of titanium(IV) alkyl-phosphate grafted silica materials that retain Ln 3+ in a solvating extraction manner. 21 The addition of nitrate salts significantly enhanced the uptake of Nd 3+ and Dy 3+ on these grafted materials, thereby suggesting that the uptake mechanism follows eq 4 . However, the addition of 5 M NH 4 NO 3 inhibited the Ln 3+ uptake on the TiP_0:1 material ( Figure S3 ).…”
Section: Results and Discussionmentioning
confidence: 91%
“… 16 20 Recently, we have shown that titanium alkyl-phosphate functionalized mesoporous silica possesses solvating extraction capability. 21 The surface alkyl chains linked to titanium phosphate moieties mimic the structure of tri- n -butyl phosphate (TBP) and hence form complexes with Ln nitrates. However, these materials seem not to be perfect candidates for intralanthanide separation because of the similar complex formation constants across the Ln series.…”
Section: Introductionmentioning
confidence: 99%
“…Now, extraction kinetics were investigated ( Figure 6 a), and the data clearly show that equilibrium is reached within only a few minutes with the lanthanides (3+), which is much faster than for other investigated systems, including commercial resins. 16 , 19 , 30 , 58 60 On the other hand, the uptake of scandium (3+) significantly increases with the extraction time, and after 1 h, no residual scandium (3+) is present in the solution. To further characterize the adsorption process and high affinity of the KIT-6-N-FGDA material toward scandium ions, adsorption experiments were performed with an initial concentration of REEs ranging from 5 to 300 μg L –1 , and Langmuir and Freundlich adsorption models were used to fit the experimental data ( Table S4 ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Regarding the inclusion of selective ligand systems, Zhang et al . recently reported mesoporous MCM‐41 silica materials functionalized by titanium alkylphosphate using a solution‐based layer‐by‐layer deposition route for enhanced uptake of rare earth ions . The overall grafted structure was inspired by the LLE extractant tri‐ n ‐butyl phosphate (TBP) (Figure ).…”
Section: Recent Progress In Spe Of Rees Using Functionalized Mesoporomentioning
confidence: 99%